Маркетингові рішення суб'єктів господарювання на вітчизняному ринку послуг з технічного обслуговування автотранспортних засобів (на прикладі ФОП Тиводар Михайло Михайлович) - Нікодемовіч, Юрій Янович; Myhalyk, Yurii Yanovych (Національний університет "Львівська політехніка", 2024)
Маркетингові рішення суб’єктів господарювання на вітчизняному ринку послуг з технічного обслуговування автотранспортних засобів відіграють важливу роль у задоволенні зростаючих потреб фізичних і юридичних осіб [1]. Від знань у сфері маркетингових досліджень і грамотної ідентифікації маркетингових проблем буде залежати вибір управлінських рішень і результати підприємницької діяльності підприємства [2, C. 27-28; 3]. Вітчизняний ринок технічного обслуговування автомобілів є одним з найбільш вагомих ринків в Україні, зважаючи на великі обсяги робіт з відновлення зруйнованої війною економіки і на зростаючу динаміку цього ринку через форс-мажорні обставин війни в країні та імпорт вживаних автомобілів. У роботі дано характеристику особливостей маркетингу послуг та їх просування у конкурентному середовищі [3; 4]. Для вибору та обґрунтування актуальності управлінських рішень використано сучасні методики з маркетингових досліджень і проведено опитування споживачів послуг, що покращує інформаційне забезпечення маркетингових рішень [5]. Об’єктом дослідження в бакалаврській роботі є підприємство, яке зареєстроване у 2017р. як ФОП Тиводар Михайло Михайлович і просуває свої послуги на ринку технічного обслуговування автотранспортних засобів. Предметом дослідження є процес розроблення та обґрунтування маркетингових рішень і методи управління маркетингом на малих і середніх підприємствах. 5 Мета дослідження - покращення діяльності ФОП Тиводар Михайло Михайлович на основі ідентифікації маркетингових проблем, вибору та обґрунтування ефективних маркетингових рішень з врахуванням факторів впливу зовнішнього середовища. Результати дослідження. На основі використання методики АВС- аналізу поєднано фінансовий і маркетинговий аналіз діяльності ФОП Тиводар Михайло Михайлович, яке просуває свої послуги на ринку з технічного обслуговування автотранспортних засобів. Визначено маркетингові проблеми даного підприємства на основі SWOT- аналізу з врахуванням ринкових ситуацій і форс-мажорних обставин в умовах війни рф проти України. Для оцінювання впливу зовнішніх чинників на маркетингову діяльність підприємств на цільовому ринку проведено аналіз політичних, економічних, соціальних і технологічних чинників і виявлено пріоритети в діяльності малих і середніх підприємств на перспективу. На основі побудованих математичних моделей тренду визначено основні тенденції розвитку ринку технічного обслуговування автотранспортних засобів в Європі і проведено порівняльну характеристику із темпами його розвитку на ринку Львівщини з врахуванням еко-орієнтованого вектору стійкого розвитку сучасної економіки. Визначено перелік ключових питань для самоаналізу діяльності ФОП Тиводар Михайло Михайлович при розробленні управлінських рішень з маркетингу і проведено анкетне маркетингове опитування споживачів послуг цього підприємства. Отримані результати маркетингового дослідження служать базою для формування маркетингової аналітики і розроблення бізнес-плану з покращення діяльності ФОП Тиводар Михайло Михайлович на ринку технічного обслуговування автотранспортних засобів.обслуговування автотранспортних засобів, маркетингові дослідження підприємства, маркетингові рішення.

Marketing decisions of business entities in the domestic market of motor vehicle maintenance services play an important role in meeting the growing needs of individuals and legal entities [1]. The choice of management decisions and the results of the enterprise's business activities will depend on knowledge in the field of marketing research and competent identification of marketing problems [2, P. 27-28; 3]. The domestic market of car maintenance is one of the most significant markets in Ukraine, given the large volumes of work on the restoration of the war-torn economy and the growing dynamics of this market due to force majeure circumstances of the war in the country and the import of used cars. The paper describes the features of marketing services and their promotion in a competitive environment [3; 4]. To select and justify the relevance of management decisions, modern marketing research methods were used and a survey of service consumers was conducted, which improves the information support for marketing decisions [5]. The object of research in the bachelor's thesis is an enterprise registered in 2017 as an individual entrepreneur Tivodar Mykhailo Mykhailovych and promoting its services in the market of technical maintenance of motor vehicles. The subject of the research is the process of developing and substantiating marketing decisions and methods of marketing management in small and medium-sized enterprises. The purpose of the research is to improve the activities of Individual Entrepreneur Tivodar Mykhailo Mykhailovych based on the identification of marketing problems, the selection and substantiation of effective marketing decisions taking into account the factors of influence of the external environment. 8 Research results. Based on the use of the ABC analysis methodology, a financial and marketing analysis of the activities of the individual entrepreneur Tivodar Mykhailo Mykhailovych, which promotes its services in the market of technical maintenance of motor vehicles, was combined. The marketing problems of this enterprise were determined based on a SWOT analysis taking into account market situations and force majeure circumstances in the conditions of the war of the Russian Federation against Ukraine. To assess the impact of external factors on the marketing activities of enterprises in the target market, an analysis of political, economic, social and technological factors was conducted and priorities in the activities of small and mediumsized enterprises for the future were identified. Based on the constructed mathematical trend models, the main trends in the development of the motor vehicle maintenance market in Europe were determined and a comparative characteristic was made with the rates of its development in the Lviv region market, taking into account the eco-oriented vector of sustainable development of the modern economy. A list of key questions for self-analysis of the activities of the individual entrepreneur Tivodar Mykhailo Mykhailovych when developing management decisions on marketing was determined and a questionnaire marketing survey of consumers of the services of this enterprise was conducted. The results of the marketing research obtained serve as a basis for the formation of marketing analytics and the development of a business plan to improve the activities of the individual entrepreneur Tivodar Mykhailo Mykhailovych in the motor vehicle maintenance market.
Marketing decisions of business entities in the domestic motor vehicle maintenance services market (on the example of Tivodar Mykhailo Mykhailovych IE)
Keywords: 6.075.00.00; маркетинг послуг; конкуренція; ринок технічного; service marketing; competition; motor vehicle maintenance market; enterprise marketing research; marketing decisions. List of used literature sources. 1. Kotler F. Fundamentals of Marketing. Classic Edition. 2023. 622 p. 2. Dykan V. L.; Kuzhavyskyi M. S. Digital Marketing as a Tool for Increasing the Value of Enterprises in the Context of Digitalization. Bulletin of the Economy of 9 Transport and Industry. 2022. No. 80. P. 21- 32.:URL:http://nbuv.gov.ua/UJRN/Vetp_2022_80_4 (access date 02.05.25) 3. Prokhorova V.; Mnykh O.; Slastianykova K.; Bezuhla J.; Us Y. Determining the Impact of the Synergic-Emergent Approach to Identification of the Matrix-Vector Level on the Development of the Competitiveness Potential of Industrial Enterprises Technological Audit and Production Reserves. 2025. Vol. 2; No. 4 (82) : Economics of Enterprises. Macroeconomics. P. 6–13. 4. Arefieva O.V.; Safonik N.P.; Dudik A.O. Strategic analysis of the development of transport enterprises in the context of innovative trends. Problems of modern transformations. Series: economics and management; 2023.URL: https://reicst.com.ua/pmt/article/view/2023-7-04-16/2023-7-04-16 (access date 06.05.25) 5. Lozynskyi T.V.; Mnykh O.B. et al. Marketing research using SPSS: a textbook. Lviv; 2020. 282 p